2013
DOI: 10.1007/s13197-013-1100-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on physicochemical composition, bioactive compounds and enzymatic activity of yellow mombin (Spondias mombin L.) tropical juice

Abstract: Yellow mombin (Spondias mombin, L.) is a tropical fruit that presents exotic taste and aroma, being source of carotenoids and phenolics compounds. It presents a good potential for processing, despite some restriction related with the presence of high amounts of peroxidase (POD) and pectinmethylesterase (PME) which can cause sensory changes in the product. This work addresses the evaluation of changes in POD and PME enzyme activity during the traditional industrial processing used to produce tropical juices in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Comparing with our results, Carvalho et al (2015) found that vitamin C content in the caja (Spondias mombin L.) was higher (13.7 ± 0, 16 mg / 100g), while antioxidant activity value was lower (2.45 ± 0.07 μmol / Trolox). Souza et al (2012) obtain high antioxidant activity and vitamin C in murici (Byrsonima crassifolia L. Rich: 57.25 ± 4.05 μmol/Trolox and 47.44 ± 3.26 mg /100 g, respectively).…”
Section: Antioxidant Activity Vitamin C and In Vitro Bioaccessibilitysupporting
confidence: 67%
See 1 more Smart Citation
“…Comparing with our results, Carvalho et al (2015) found that vitamin C content in the caja (Spondias mombin L.) was higher (13.7 ± 0, 16 mg / 100g), while antioxidant activity value was lower (2.45 ± 0.07 μmol / Trolox). Souza et al (2012) obtain high antioxidant activity and vitamin C in murici (Byrsonima crassifolia L. Rich: 57.25 ± 4.05 μmol/Trolox and 47.44 ± 3.26 mg /100 g, respectively).…”
Section: Antioxidant Activity Vitamin C and In Vitro Bioaccessibilitysupporting
confidence: 67%
“…A sour taste is fairly typical of this fruit, which presents total titratable acidity ranging from 1.0 to 1.6% citric acid and pH between 2.49 to 2.9, i.e. properties that confer such taste (Canuto et al, 2010;Carvalho et al, 2015;Gadelha et al, 2009). This high acidity is responsible for influencing the structure of the gel, thus promoting syneresis (Danalache et al, 2015b).…”
Section: Cata Test Analysismentioning
confidence: 99%
“…Therefore, several studies were performed to evaluate the effect of HTLT treatments on these activities. Examples include: (1) the reduction of PME enzymatic activity by 75% to 83%, respectively, in yellow mombin juice (de Carvalho and others ) and litchi‐based beverage (Swami Hulle and Rao ), or its complete inactivation in pear juice (Saeeduddin and others ), and broccoli/carrot/red pepper/tomato smoothie (Rodríguez‐Verástegui and others ); (2) the reduction of PPO enzymatic activity by 79% in litchi‐based beverage (Swami Hulle and Rao ), or its total inactivation in smoothie (Rodríguez‐Verástegui and others ), pear juice (Saeeduddin and others ), and longan juice added with xanthan (Chaikham and Apichartsrangkoon ); (3) the reduction of POD enzymatic activity by 78% and 97.5% in litchi‐based beverage (Swami Hulle and Rao ) and yellow mombin juice (de Carvalho and others ), respectively, as well as its complete inactivation in pear juice (Saeeduddin and others ), in a juice‐blend mixed with soymilk (Morales‐de la Peña and others ), and a vegetable‐based smoothie (Rodríguez‐Verástegui and others ); and (4) the reduction of LOX enzymatic activity by 51% in kiwifruit/orange/pineapple juice blend mixed with soymilk (Morales‐de la Peña and others ).…”
Section: Thermal Treatmentsmentioning
confidence: 99%
“…In jobo, 11 different carotenoids were differentiated according to a combination of both UV-Vis and MS spectral data, elution order, available standards and various reports [42][43][44]. The total carotenoid content was 45.8 (± 3.1) µg g −1 fw, with β-cryptoxanthin, α-carotene and β-carotene showing a relative abundance of 25.4%, 10.5% and 8.5%, respectively.…”
Section: Jobo Fruitmentioning
confidence: 99%